Poly(p-phenylene)-based membranes with cerium for chemically durable polymer electrolyte fuel cell membranes - Abdul Kodir; Seunghee Woo; Sang-Hun Shin; Soonyong So; Duk Man Yu; Hyejin Lee; Dongwon Shin; Jang Yong Lee; Seok-Hee Park; Byungchan Bae (Heliyon, 2024)
A poly(p-phenylene)-based multiblock polymer is developed with an oligomeric chain extender and cerium (CE-sPP-PPES + Ce3+) to realize better performance and durability in proton exchange membrane fuel cells. The membrane performance is evaluated in single cells at 80 °C and at 100% and 50% relative humidity (RH). The accelerated stability test is conducted 90 °C and 30% RH, during which linear sweep voltammetry and hydrogen permeation detection are monitored periodically. Results demonstrate that the proton conductivity of the pristine hydrocarbon membranes is superior to that of PFSA membranes, and the hydrogen crossover is significantly lower. In addition, a composite membrane containing cerium performs similarly to a pristine membrane, particularly at low RH levels. Adding cerium to CE-sPP-PPES + Ce3+ membranes improves their chemical durability significantly, with an open circuit voltage decay rate of only 89 μV/h for 1000 h. The hydrogen crossover is maintained across accelerated stability tests, as confirmed by hydrogen detection and crossover current density. The short-circuit resistance indicates that membrane thinning is less likely to occur. Collectively, these results demonstrate that a hydrocarbon membrane with cerium is a potential alternative for fuel cell applications.